The petrogenesis and mineralization of Zhaojinggou Nb–Ta deposit, Inner Mongolia: Evidence from geochronology, rock, and mineral geochemistry. Issue 5 (5th March 2023) - Li, Xue; Wang, Keyong; Sun, Guosheng; Zhang, Jitian; Liu, Genyi; Ma, Dong; Sun, Jiuda; He, Xin; Wang, Guangwei
Abstract : The Zhaojinggou Nb–Ta deposit is one of large rare metal deposits newly discovered in the northern margin of the North China Craton in recent years. This paper reports petrography, petrochemistry, columbite‐group minerals U–Pb chronology study of the amazonite granitic pegmatite (AGP) exposed in this deposit, and composition of columbite‐group minerals and biotite are obtained by electron probe microanalyzer and LA‐ICP‐MS. Eighteen analyses of columbite‐group minerals yielded weighted mean 206 Pb/ 238 U age of 116.9 ± 1.4 Ma. The crystallization temperature of biotite is 630–650°C, and the oxygen fugacity is 10 −17 –10 −18 bars. The biotite has low MgO contents and high Rb, Rb/Sr, and FeO T /(FeO T + MgO) ratios. The AGP has extremely low MgO, Cr, Co and Ni contents, with Nb/Ta ratios range from 1.63 to 9.05 and Rb/Sr ratios range from 303.30 to 648.90, and obvious 'M' type tetrad effect of rare earth element indicating that the formation of the AGP is related to crust‐derived magma. The contents of Nb2 O5 and FeO decrease, while the Ta2 O5 and WO3 contents, Mn # and Ta # values increase gradually from the core to the rim of columbite‐group minerals. Some columbite‐group minerals have unobvious oscillatory zoning, and some have a clear bright zoing with high Ta contents on the rim, indicating that the genesis of Zhaojinggou Nb–Ta deposit is mainly magmatic crystallization differentiation, accompanied by hydrothermal autometasomatism in the late stage. Abstract : The deposit was formed in an extensional tectonic background in the late Yanshanian, magma was formed by partial melting of Nb–Ta‐rich lower crust, undergoing high evolution. Mineralization is crystallization differentiation and hydrothermal self‐metasomatism